Tindak Pidana Korupsi Di Era Pandemic Global - herman suherman (Universitas Islam Bandung, 2020)
Corruption is a serious crime in Indonesia that has destroyed the foundation of the state and nation. Not Only is corruption destrimental to the state, but it also snatches social right and economic developmens in general.This crime is very difficult to eradicate, because it is often committed through a systematic way and involved the people who hold economic and political power. The impacts of corruption are devastating. to overcome the problems can be formulated policy formulation of capital punishment law against perpetrators of corruption in Indonesia in the future by making some exceptions and change to article 2 in Law no. 20 ofP 2001 on amendment to Law Number 31 year 1999 concerning the Eradication of Corruption.